The role of potassium channels in the endothelial dysfunction induced by periodontitis - Luiz Renato Olchanheski JR; Regina Sordi; Junior Garcia Oliveira; Gustavo Ferreira Alves; Reila Taina Mendes; Fábio André Santos; Daniel Fernandes (University of São Paulo, 2018)
Abstract Objective: Periodontitis is associated with endothelial dysfunction, which is clinically characterized by a reduction in endothelium-dependent relaxation. However, we have previously shown that impairment in endothelium-dependent relaxation is transient. Therefore, we evaluated which mediators are involved in endothelium-dependent relaxation recovery. Material and methods: Rats were subjected to ligature-induced experimental periodontitis. Twenty-one days after the procedure, the animals were prepared for blood pressure recording, and the responses to acetylcholine or sodium nitroprusside were obtained before and 30 minutes after injection of a nitric oxide synthase inhibitor (L-NAME), cyclooxygenase inhibitor (Indomethacin, SC-550 and NS- 398), or calcium-dependent potassium channel blockers (apamin plus TRAM- 34). The maxilla and mandible were removed for bone loss analysis. Blood and gingivae were obtained for C-reactive protein (CRP) and myeloperoxidase (MPO) measurement, respectively. Results: Experimental periodontitis induces bone loss and an increase in the gingival MPO and plasmatic CRP. Periodontitis also reduced endothelium-dependent vasodilation, a hallmark of endothelial dysfunction, 14 days after the procedure. However, the response was restored at day 21. We found that endothelium-dependent vasodilation at day 21 in ligature animals was mediated, at least in part, by the activation of endothelial calcium-activated potassium channels. Conclusions: Periodontitis induces impairment in endothelial-dependent relaxation; this impairment recovers, even in the presence of periodontitis. The recovery is mediated by the activation of endothelial calcium-activated potassium channels in ligature animals. Although important for maintenance of vascular homeostasis, this effect could mask the lack of NO, which has other beneficial properties.